Strong TCRγδ Signaling Prohibits Thymic Development of IL-17A-Secreting γδ T Cells - Sumaria, Nital (Cell Rep, 2017)
Despite a growing appreciation of γδ T cell contributions to numerous immune responses, the mechanisms that underpin their thymic development remain poorly understood. Here, using precursor/product relationships, we identify thymic stages in two distinct developmental pathways that generate γδ T cells pre-committed to subsequent secretion of either IL-17A or IFNγ. Importantly, this framework for tracking γδ T cell development has permitted definitive assessment of TCRγδ signal strength in commitment to γδ T cell effector fate; increased TCRγδ signal strength profoundly prohibited the development of all IL-17A-secreting γδ T cells, regardless of Vγ usage, but promoted the development of γδ progenitors along the IFNγ pathway. This clarifies the recently debated role of TCRγδ signal strength in commitment to distinct γδ T cell effector fates and proposes an alternate methodology for the study of γδ T cell development.